A narrative review of gaps in the provision of integrated care for noncommunicable diseases in India - Manoj Kumar Pati; N. Swaroop; Arin Kar; Preeti Aggarwal; Krishnamurthy Jayanna; Wim Van Damme (Frontiers Media S.A., 2020)
Abstract Background Low- and middle-income countries (LMICs) account for a higher burden of noncommunicable diseases (NCD) and home to a higher number of premature deaths (before age 70) from NCDs. NCDs have become an integral part of the global development agenda; hence, the scope of action on NCDs extends beyond just the health-related sustainable development goal (SDG 3). However, the organization and integration of NCD-related health services have faced several gaps in the LMIC regions such as India. Although the national NCD programme of India has been in operation for a decade, challenges remain in the integration of NCD services at primary care. In this paper, we have analysed existing gaps in the organization and integration of NCD services at primary care and suggested plausible solutions that exist. Method The identification of gaps is based out of a review of peer-reviewed articles, reports on national and global guidelines/protocols. The gaps are organized and narrated at four levels such as community, facility, health system, health policy and research, as per the WHO Innovative Care for Chronic Conditions framework (WHO ICCC). Result The review found that challenges in the identification of eligible beneficiaries, shortage and poor capacity of frontline health workers, poor functioning of community groups and poor community knowledge on NCD risk factors were key gaps at the community level. Challenges at facility level such as poor facility infrastructure, lack of provider knowledge on standards of NCD care and below par quality of care led to poor management of NCDs. At the health system level, we found, organization of care, programme management and monitoring systems were not geared up to address NCDs. Multi-sectoral collaboration and coordination were proposed at the policy level to tackle NCDs; however, gaps remained in implementation of such policies. Limited research on the effect of health promotion, prevention and, in particular, non-medical interventions on NCDs was found as a key gap at the research level. Conclusion This paper reinforces the need for an integrated comprehensive model of NCD care especially at primary health care level to address the growing burden of these diseases. This overarching review is quite relevant and useful in organizing NCD care in Indian and similar LMIC settings.